The Use of Language Function in Maybelline New York Cosmetic Advertisements - Ayu Kartika Septiana (WACANA : MAJALAH ILMIAH TENTANG BAHASA, SASTRA DAN PEMBELAJARANNYA, 2022)
This article discusses the use of language function in Maybelline New York Cosmetic advertisements. The theory which was applied inanalysing the data and used as the main theory is taken from the book proposed by Roman Jakobson entitled The Framework of Language published in 1980. The data were taken from the advertisements of Maybelline New York Cosmeticaround 2015 until 2019 which was downloaded from YouTube. The analyse method that is used in this paper is descriptive qualitative method. Based on the result of the analysis, there are five from six kinds of language function found in Maybelline New York cosmetic advertisements, they are referential, emotive, conative, phatic, and poetic function but there’s no metalingual function.